Family Management Perspective Islamic Education (A Case Study in Southeast Sulawesi and Yogyakarta) - Subiyantoro Subiyantoro (Universitas Darussalam Gontor, 2022)
This study aimed to determine the family management perspective of Islamic education in rural communities in Yogyakarta and Southeast Sulawesi. The data was collected by observation, in-depth interviews, and documentation. The results show that family management means a family arrangement in preparing various resources for family needs. The farming community in Atula Village, Southeast Sulawesi defined Islamic education as follows; first, it is something that is important and must be done, to gain knowledge, provision for later life, to add insight, future, experience, find work, become smart, then put it into practice, so parents prepare finances for their children. Second, the Islamic education that is carried out by the children of the farming community in the Atula village is Madrasah and Islamic boarding school, generating and exploring the potential for the progress of the nation and generations through Islam. As for Banjaroya Village, Yogyakarta, the majority of parents' occupations are farmers, the meaning of Islamic education for them is; first in general (mostly parents), do not have a clear plan about the education of their children. Second, children and parents are less interested in schooling their children in Madrasas or Islamic boarding schools. The community also viewed religious education is seen as less